MANUSIA BERKUALITAS DALAM PANDANGAN AL-QUR’AN - Mujiburrohman Mujiburrohman (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
Humans are the most fascinating creatures, unique, multi-dimensional creatures, all-encompassing, open-minded, and have great potential. Therefore, Karen Horny (Psychology expert), said that "quality people are people who have been able to balance the impulses in themselves, as to realize harmonious behavior. He is able to connect with his environment, able to create safe and harmonious. He is not aggressive, does not alienate himself from his environment, and his life does not depend on others. "In the Qur'an, humans are repeatedly elevated because of the positive actualization of their minds; Al-Qur'an says that human beings are "hanif" which is inclined to the truth, monotheism of God, and other noble values. The verses of Al-Qur’an which explain humanity are of very high quality. The terms or verses are interrelated and explain each other. So, if you take one of the terms of the terms used by Al-Qur’an, then the description will complement each other and be characteristic of the others. It can be said that the concepts and characteristics of human quality are not single, but are comprehensive and complementary.